International Transport Workers' Journal : monthly publication of the ITF = ITF journal. - International Transport Workers' Federation (ITF) (London : ITF, 1942)
Bibliotheek Camille Huysmans
Engels
Periodiek
Keywords: Internationale Transportarbeiders Federatie (ITF).; syndicale pers